Using film screenings to explore the nature and impact of student interactions with the Observatory informal settlement - Miza, Kamvalethu (Department of Sociology, 2025)
This master's thesis presents a detailed exploration of student interactions within the Observatory Informal Settlement OIS during film screenings, employing a qualitative approach deeply rooted in social exchange, intergroup contact, and social identity theoretical underpinnings. Against the complex social dynamic of Observatory and the historical backdrop of South Africa, the study investigates the dynamics that shape perceptions, interactions, and potential positive outcomes in this diverse community. Curated by Khululekile Banzi, a resident of OIS, the communal space created during film screenings serves as a unique platform for both entertainment and education. UCT students, particularly those residing in Obz Square, engage with OIS residents amidst challenges posed by language barriers, historical contexts, and personal characteristics. The study delves into the transformative potential embedded in sustained engagement, unravelling the interplay between preconceived notions and the realities that emerge through genuine, prolonged interaction. External factors shaping these interactions, including the accessibility of film screenings and the deliberate creation of a welcoming environment, are explored to reveal their profound impact on the nature and quality of engagements between students and OIS residents. Through its theoretical underpinnings the study delves into the complex dynamics of identity, belonging, reciprocity, and understanding. Chapter Five, a focal point of humanizing the OIS narrative, reveals personal connections, shared experiences, and the resilience of the community-driven initiative as crucial elements in reshaping perceptions and encouraging meaningful connections. The theoretical underpinnings explore these interactions, showing the communal nature of shared experiences and rituals while addressing challenges and overcoming prejudices. The film screening emerge as transformative space for negotiation of social identities, fostering a sense of shared belonging. Resilience becomes a defining thread, not only within OIS but as a powerful mechanism for positive change within marginalized communities. The recommendations presented in this thesis transcend academic suggestions, constituting a call for action and a blueprint for sustainable growth, echoing the transformative power of intentional and sustained engagement. The OIS, as a microcosm of resilience and positive change, stands not only as a case study but as an inspiration and a call to join hands in building a more inclusive, understanding, and resilient society.